Pengaruh Kompetensi Profesional Guru Pendidikan Agama Kristen Terhadap Hasil Belajar Peserta Didik - Samosir, Bungatiur Englis; Naibaho, Dorlan (Jurnal Pendidikan dan Pembelajaran, 2022)
This study tested the significant impact of the professional competence of Christian teachers on the students' study. Because of the complexity of today's educational needs, the teacher's role in guiding and motivating students becomes essential. Especially in the context of Christian religious education, where spiritual and ethical values are central, teacher competence can play an important role in shaping students' understanding and impact on religious education. Christian religious education teachers are required not only to have a deep understanding of religious education but also to have strong pedagogy abilities. The purpose of this study is to know the extent of the competence affects the students' learning results. With data collection through surveys, interviews, and class observations, this study aims to describe the complex relationship between teacher competence and student achievement. One of the main results of this study is teachers with high professional competence tend to create a more pleasant learning environment. He knows how to integrate religious education into everyday life so that learning becomes more meaningful and interesting to students.